The Effect of Islamic Leadership on Employee Performance Mediated by Job Satisfaction - Riska Fauziyah Amelia; Rizki Febriani; Chalimatuz Sa'diyah (Universitas Muhammadiyah Malang, 2022)
This study aims to determine how the influence of Islamic leadership on employee performance, to determine the effect of job satisfaction on employee performance, and to determine whether job satisfaction plays a role in mediating Islamic leadership on employee performance. This research was conducted on the workforce of the Lumajang Islamic Hospital with a total of 68 respondents. Sampling technique uses a saturated sampling technique and data collection using a questionnaire. The data analysis using SEM-PLS. The results of this study indicate that Islamic leadership has an effect on employee performance, Islamic leadership has an effect on job satisfaction, job satisfaction has no effect on employee performance, and Islamic leadership has a role in mediating job satisfaction on employee performance.